Pulse oximetry values of neonates admitted for care and receiving routine oxygen therapy at a resource‐limited hospital in Kenya. (27th October 2017) - Morgan, Melissa C; Maina, Beth; Waiyego, Mary; Mutinda, Catherine; Aluvaala, Jalemba; Maina, Michuki; English, Mike
Abstract : Aim: There are 2.7 million neonatal deaths annually, 75% of which occur in sub‐Saharan Africa and South Asia. Effective treatment of hypoxaemia through tailored oxygen therapy could reduce neonatal mortality and prevent oxygen toxicity. Methods: We undertook a two‐part prospective study of neonates admitted to a neonatal unit in Nairobi, Kenya, between January and December 2015. We determined the prevalence of hypoxaemia and explored associations of clinical risk factors and signs of respiratory distress with hypoxaemia and mortality. After staff training on oxygen saturation (SpO2 ) target ranges, we enrolled a consecutive sample of neonates admitted for oxygen and measured SpO2 at 0, 6, 12, 18 and 24 h post‐admission. We estimated the proportion of neonates outside the target range (≥34 weeks: ≥92%; <34 weeks: 89–93%) with 95% confidence intervals (CIs). Results: A total of 477 neonates were enrolled. Prevalence of hypoxaemia was 29.2%. Retractions (odds ratio (OR) 2.83, 95% CI 1.47–5.47), nasal flaring (OR 2.68, 95% CI 1.51–4.75), and grunting (OR 2.47, 95% CI 1.27–4.80) were significantly associated with hypoxaemia. Nasal flaring (OR 2.85, 95% CI 1.25–6.54), and hypoxaemia (OR 3.06, 95% CI 1.54–6.07) were significantly associated with mortality; 64% of neonates receiving oxygen were out of range at ≥2 time points and 43% at ≥3 time points. Conclusion: There is a high prevalence of hypoxaemia at admission and a strong association between hypoxaemia and mortality in this Kenyan neonatal unit. Many neonates had out of range SpO2 values while receiving oxygen. Further research is needed to test strategies aimed at improving the accuracy of oxygen provision in low‐resource settings.